PEMILIHAN DAN PENEMPATAN BALEINE PADA KAMISOL SEBAGAI PELENGKAP BUSANA PESTA - Ariyana Damayanti; Yulia Rike Anjarsari (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2020)
Camisole is one of the underwear that is commonly used to improve body shape so that it looks more beautiful and proportional. Most of the camisole is made by using a baleine stitch and attachd to the main material, this time the writer wants to try new things in making a camisole. Such as selection and placement Baleine on a camisole as a complement to a party outfit. The objectives of this research are: 1) To know the right type of baleine on a camisole; 2) Can know the placement of baleine on a camisole. The methods used in the selection and placement of baleine on a camisole as a complement to the party dress are: 1) R&D method; 2) Data Analysis. The selection and placement of Baleine on the camisole as a complement to the party outfit begins with determining the design. Camisole design to be made, preparation of tools and materials, taking measurements, making basic patterns, breaking patterns, cutting steps, and determining baleinejahit and baleine stitches that will be installed on the main material or will be attached to the furing (sewing process). Baleine installation can be done in two ways, namely attaching it to the main material and attaching it to the lining. It turns out that baleine sewing is more effective for making camisole, the result of a camisole that uses baleine sewing looks firm and good when used.